Comparative analysis of the methods of watermarking X-ray images - Kulbaka, Weronika; Paluch, Paulina; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2021)
This paper is devoted to the comparative analysis of watermarking algorithms for X-ray images. The techniques based on discrete wavelet transform (DWT), singular value decomposition (SVD) and DWT-SVD hybrid were compared. Transparency, resistance to graphical transformations, and performance were investigated. The watermarked images were visually evaluated and quality tested. SVD showed the highest resistance to attacks, and the embedded watermarked images were of better quality in the comparison to the other algorithms. The DWT technique was the fastest, but not resistant to graphical transformations. In DWT-SVD labeled images, the watermark is indistinguishable, but the resistance to attacks is low. The SVD was found to be the most suitable method for watermarking of X-ray images.